Character-Based Curriculum Development Strategy for Education Units in Elementery Schools - Fradana, Ahmad Nurefendi; Putri, Arinda Salsabila; Aulia, Nur Fikah Afi; Amalia, Haidar; Laily, Risha Dwi Nur (Procedia of Social Sciences and Humanities, 2024)
This research examines character-based curriculum development strategies in elementary schools. The applied research approach includes document analysis, observation, and in-depth interviews with teachers and decision makers in the education sector. This research shows that integrating a character-based curriculum can not only improve academic achievement, but also improve students’ moral and ethical values. Implementing this strategy requires full support from all stakeholders, including teacher training and professional development. These results highlight the importance of a comprehensive approach to curriculum development that focuses not only on cognitive aspects but also on student personality development.